Pelaksanaan Pembelajaran Menulis Teks Deskripsi Siswa Kelas VII.1 MTS Negeri 2 Kaur - Sarif Ahmad; Suhartono Suhartono; Susetyo Susetyo (LP4MK STKIP PGRI Lubuklinggau, 2020)
Learning to write description texts is carried out by Indonesian language teachers with a variety of strategies. The strategy used by the teacher aims to achieve the learning objectives of students being able to write description texts well. For this reason, explanations are needed regarding the implementation of writing description texts, especially for students of class VII.1 MTs Negeri 2 Kaur. The research method used was descriptive qualitative research. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. Test the validity of the data using triangulation of data sources. The results showed that the implementation of Indonesian language learning material to write a description text for grade VII.1 MTs Negeri 2 Kaur students was good enough. The teacher has used a scientific approach that is observing, asking, exploring, associating, and communicating. Learning activities carried out in three stages: first, preliminary activities, the teacher makes apperception, motivation, and delivery of learning objectives. Second, the core activity of learning, the teacher invites students to understand the notion of descriptive text, identify the structure of the text, and correct errors in the use of punctuation / spelling. Third, the closing activity, the teacher concludes the learning material by involving students in order to know the students' abilities during the learning process. The learning steps taken by the teacher are in accordance with what is written in the Learning Implementation Plan (RPP).